Modern Languages French/Spanish: Cycle 1 (Forms 1-3) Draft Syllabus for National Certificate of Secondary Education - Trinidad and Tobago, Ministry of Education, Curriculum Division (Ministry of Education, 1994)
This syllabus is intended to achieve the two major objectives of Cycle 1 of the foreign language programme designed for all schools in Trinidad and Tobago, that is 1) to help students achieve a minimum level of communicative proficiency or competence in the foreign language, and 2) to provide students with foundation for achieving their goals at Cycle II (Forms 4 and 5) and Cycle III (Form 6).
Keywords: National Certificate of Secondary Education